Complementarities Between Organizational IT Architecture and Governance Structure - Tiwana, Amrit; Konsynski, Benn (Information Systems Research, 2010)
This study addresses the theoretically neglected interplay between organizational information technology (IT) architecture and IT governance structure in shaping IT alignment. We theoretically develop the idea that IT architecture modularity helps sustain IT alignment by increasing IT agility, and that decentralization of IT governance strengthens this relationship. IT architecture therefore complements IT governance structure. Tests of the proposed mediated-moderation model using data from 223 organizations support these ideas. Implications for theory and practice are also discussed.